A two-years real-word study with fingolimod: early predictors of efficacy and an association between EBNA-1 IgG titers and multiple sclerosis progression - Dominguez-Mozo, Maria Inmaculada; Galán, Victoria; Ramió-Torrentà, Lluís; Quiroga, Ana; Quintana, E.; Villar, Luisa María; Costa-Frossard, Lucienne; Fernández-Velasco, José Ignacio; Villarrubia, Noelia; Garcia-Martinez, María Angel; Arroyo, Rafael; Alvarez-Lafuente, Roberto (Frontiers in Immunology, 2024)
Although fingolimod has shown to be an effective treatment reducing relapse rate and also slowing down the disability progression in relapsing-remitting multiple sclerosis (RRMS) patients, it is important to quickly identify those suboptimal responders.The main objective was to assess different clinical, radiological, genetic and environmental factors as possible early predictors of response in MS patients treated with fingolimod during 24 months.The secondary objective was to analyze the possible contribution of the environmental factors analyzed to the progression and activity of the disease along the 2-years of follow-up.A retrospective study with 151 patients diagnosed with MS, under fingolimod treatment for 24 months, with serum samples at initiation and six months later, and with clinical and radiological data at initiation and 24 months later, were included in the study. Clinical and radiological variables were collected to establish NEDA-3 (no evidence of disease activity: patients without relapses, disability progression and new T2 lesions or Gd+ lesions) and EDA (evidence of disease activity: patients with relapses and/or progression and/or new T2 lesions or Gd+ lesions) conditions. HLA-II, EBNA-1 IgG and VCA IgG from EBV and antibody titers against HHV-6A/B were also analyzed.A total of 151 MS patients fulfilled the inclusion criteria: 27.8% was NEDA-3 (37.5% among those previously treated with high efficacy therapies >24 months).The following early predictors were statistically significantly associated with NEDA-3 condition: sex (male; p=0.002), age at baseline (older; p=0.009), relapses 2-years before fingolimod initiation ≤1 (p=0.010), and absence of Gd+ lesions at baseline (p=0.006).Regarding the possible contribution of the environmental factors included in the study to the activity or the progression of the disease, we only found that EBNA-1 IgG titers decreased in 20.0% of PIRA (progression independent from relapse activity) patients vs. 73.3% of RAW (relapse-associated worsening) patients (p=0.006; O.R.=11.0).MS patients that are male, older, and with a low clinical and radiological activity at fingolimod initiation have a greater probability to reach NEDA-3 condition after two years with this therapy. An intriguing association of EBV with the progression of the disease has also been described, but it should be further study in a larger cohort to confirm these results.